Regioselective acylation of 2-methoxy naphthalene catalyzed by supported 12-phosphotungstic acid - Kumaraguru, Thenkrishnan; Devi, Ayala Vedamayee; Siddaiah, Vidavalur; Rajdeo, Kishor; Fadnavis, Nitin W. (Applied Catalysis A-General, 2014)
12-Phosphotungstic acid supported on silica gel, zirconium sulfate, and a combination of silica gel and zirconium sulfate (50% w/w) were employed as solid acid catalysts for regioselective acylation of 2-methoxynaphtalene with acetic anhydride. 1-(6-Methoxynaphthalen-2-yl)ethanone (2,6-AMN), a commercially important intermediate for production of Naproxen, was obtained with excellent selectivity (>98%) at 67-68% conversion using 12-phosphotungstic acid supported on silica gel 20% (w/w) in refluxing tetrachloroethane. The unreacted starting material can be easily separated from the product by a simple crystallization from nonane. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Acylation; Naproxen; Phosphotungstic acid; Silica gel; Supported; Zirconium sulfate